Women informal workers’ domestic decision- making: A Longwe framework analysis - Hidayanti, Alifvia Ridzky; Arsi, Antari Ayuning (Universitas Muhammadiyah Malang, 2026)
This study examines the limitations of Longwe's Women Empowerment Framework, which assumes a linear progression and conceptualizes control as the final stage of women's empowerment. The study focuses on domestic decision-making among women informal workers across generations and explores whether this linear assumption remains relevant within patriarchal contexts. The research conducted in Tanjung Priok, North Jakarta, with Generations X, Y, and Z positioned as descriptive contexts rather than comparative variables. A qualitative approach was employed, involving nine informants selected through purposive sampling. Data collected through in-depth interviews and observations, and analyzed using Longwe's framework, extended by Lukes perspective on power relations and Kandiyoti's concept of the patriarchal bargain. The findings identify three patterns of domestic decision-making: decision-making without negotiation, limited negotiation, and independent negotiation shaped by socio-cultural norms, children, economic conditions, and educational background. The study concludes that domestic decision-making among women informal workers is highly contextual and cannot be adequately understood through a linear empowerment framework. This research contributes to the literature by demonstrating that control in domestic decision-making is fragmented and domain-specific within the lived realities of women's informal workers in urban settings. Penelitian ini memperluas keterbatasan dalam Kerangka Pemberdayaan Perempuan Longwe yang memiliki asumsi linearitas dan memandang kontrol merupakan tahap akhir dalam mencapai pemberdayaan perempuan. Fokus penelitian ini menganalisis pengambilan keputusan domestik perempuan pekerja informal lintas generasi dan meneliti apakah linearitas masih relevan dalam konteks patriarki. Penelitian dilakukan di Tanjung Priok, Jakarta Utara dengan generasi X, Y dan Z sebagai konteks deskriptif. Menggunakan pendekatan kualitatif dengan total sembilan informan yang dipilih menggunakan sampel bertujuan. Data dikumpulkan melalui wawancara dan observasi mendalam lalu dianalisis menggunakan Kerangka Longwe yang diperluas dengan perspektif relasi kuasa oleh Lukes dan konsep Patriarchal Bargain oleh Kandiyoti. Ditemukan terdapat tiga variasi pola pengambilan keputusan, yaitu keputusan tanpa negosiaasi, negosiasi terbatas, dan negosiasi mandiri. Pola tersebut terbentuk dari faktor-faktor yang dipengaruhi oleh norma sosial kultural, anak, ekonomi, dan pendidikan. Penelitian ini menyimpulkan bahwa pengambilan keputusan domestik perempuan pekerja informal bersifat kontekstual dan tidak dapat dipahami menggunakan kerangka pemberdayaan yang linear. Penelitian ini memberikan kontribusi bahwa kontrol pada pengambilan keputusan sifatnya terfragmentasi dan ranah-spesifik dalam konteks perempuan pekerja informal di wilayah urban.